Choice of tree species in the aftermath of two major storms : a qualitative study of private forest owners in southern Sweden - Lodin, Isak (SLU/Southern Swedish Forest Research Centre, 2016)
The forests in Götaland, the most southern part of Sweden, are dominated by Norway spruce (Picea abies (L.) H. Karst). This species is very important for the Swedish forest sector, but also associated with certain risks, such as wind-throw. Götaland was hit by the storm Gudrun in 2005, causing damages of a magnitude never experienced in the modern Swedish history. Two years later the same region suffered severe damages in another storm, Per. Due to the ownership structure in southern Sweden the reforestation efforts after the storms were largely made by small-scale private forest owners. Disproportionally high losses of Norway spruce exposed the risks associated with previous practices. In addition, reforestation grants were available through the Swedish Forest Agency that compensated for the higher regeneration costs associated with broadleaves. Despite this, the vast majority of the storm felled areas were regenerated with Norway spruce. Through qualitative interviews and subsequent analysis, this study examined how small-scale private forest owners’ reasoned in their choice of species and which factors that were of decisive importance for the final outcome. Regeneration with Norway spruce was mainly an expression of forest owners evaluating the different alternatives based on economic rationality. Past and current economic conditions have been and still are favorable for this species, and forest owners therefore relayed on experiencebased knowledge in their reforestation decision. Meanwhile, there are other contextual factors that steered forest owners towards planting spruce, such as a high browsing pressure and influence from dominant forest management norms. Regeneration with other species reflects situations where forest owners incorporated other aspects in their decision-making processes. Regeneration with broadleaves was favored by consideration of aesthetical values and an awareness of potential future risks with Norway spruce. In addition, since large areas had to be regenerated, forest owners ceased the opportunity to vent their curiosity with new species (especially exotic conifers/broadleaves) on smaller areas. The soft policy instruments that characterize Swedish forest policy also had a facilitating effect. Forest owners received information about alternatives through various pathways and the reforestation grants were of crucial importance for the owners that planted broadleaves. This study also suggests that the higher share of naturally regenerated birch found in regenerations surveys after Gudrun cannot simply be regarded as an effect of lower level of ambition, but also expresses a shift towards a more positive attitude concerning this species.